Estimating the error of coordinate measuring machines - Wilke, Fabiana Zamora; de Oliveira, João Batista S. (Computer Assisted Methods in Engineering and Science, 2023)
This paper presents a strategy to analyze the accuracy of measurements obtained in the calibration process of a Coordinate Measuring Machine (CMM). Thereafter, the operator will be able to find the most appropriate placement region for a part to be analyzed in order to reduce the error and take into account the shape of each part. Such strategy was developed through the visualization of error contours in the measurement space. Five different error indexes were developed for this analysis, associating different values to each point of the measurement space, allowing the user to choose the aspect he wants to take into consideration in the measurement process: centering of samples, dispersion, average errors, and others. Finally, the results are transformed into images, analysed and compared.